Socio-economic reforms in line with Maqasid Al-Shariah (the case of Caliph Umar ibn Abd Al-Aziz) - Tahir, Ibrahim Nuhu (ISTAC, 2015)
Abstract The paper addresses the practical approach of the rightly guided caliph Umar ibn Abd Al-Aziz. Its emphasis is on the unique and successful methods used by this exceptional leader. He led the Muslim community with justice and this in itself helped regain the prestige of the Muslim land as a healthy, successful and peaceful society. The reforms he employed helped the society achieve not How did he manage to alleviate poverty to the extent that all Muslims did not need charity during his reign? Success lies in re-tracing the footsteps of those who are regarded as role models that provide a better example for later generations to emulate. What could possibly have the power to rejuvenate a failing society such as ours other than the realization of the awareness of Allah the All-Mighty over everything? Thus the paper will suggest some practical utilization of those above indicated methods that the government in our current society can emulate in order to ensure a better future for human socio-economic development. The main bases of this research are the historical facts and data addressing the current situation of the Muslim community.